Impact of Farm Size and Sociodemographic Characteristics on Agricultural Households’ Food Security - Kadir, K; Prasetyo, Octavia Rizky (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2023)
Most agricultural households in Indonesia are small-scale farmers making them prone to food insecurity. Until recently, no study has assessed the impact of farm size and sociodemographic characteristics on the food insecurity status of agricultural households using a nationwide agricultural household survey in Indonesia. Our study aims to address this gap by utilizing the results of the first Indonesian Agricultural Integrated Survey conducted by BPS in 2021. Applying the Rasch Model and Multinomial Logistic Regression, we found that the farm size has a positive impact in lowering the probability of agricultural households experiencing moderate or severe levels of food insecurity. Our study also found that agricultural households with a higher probability of being food insecure are characterized by having higher members of households, relying only on agriculturalactivities for their livelihood, lower education attainment of household heads, and being led by female farmers. Our study recommends improving the farmers’ agricultural scale by focusing on the improvement of the yield. It can be done through the adoption of mechanization and digital technology. Moreover, we also recommend a social assistance programme for food security targeting agricultural households with characteristics identifiedin our findings.